Investigating associations between horse hoof conformation and presence of lameness - Mata, Fernando (2024)
Hoof trimming and shoeing determine the horse’s hoof shape and balance. Hoof conformation plays a crucial role in limb biomechanics and can consequently prevent or predispose to injury. This study investigated the relationship between the morphometric characteristics of the horse’s hoof, specifically, the dorsal hoof wall angle (DHWA), the coronet band circumference (CBC), and lameness in 73 horses categorised as undertaking either show jumping, dressage, or riding school activities. Results from logistic regression indicated that horses with either a combination of acute DHWA with large CBC, or more upright feet with larger DHWA and smaller CBC have higher probabilities of lameness. Show jumping and dressage horses showed a higher prevalence of lameness. Hoof morphometry should be monitored, and podiatric interventions should be regularly scheduled for the maintenance of correct hoof conformation to prevent injury. This study suggests that an aligned hoof–pastern axis managed by a DHWA of around 50 degrees may prevent lameness, with special emphasis on horses in dressage and show jumping activities. On the other hand, we can also speculate that the disturbed axis alignment of DHWA may be a cause of lameness.